2013
DOI: 10.1152/ajpregu.00245.2012
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin and myokine involvement in the cyclooxygenase-inhibiting drug enhancement of skeletal muscle adaptations to resistance exercise in older adults

Abstract: Twelve weeks of resistance training (3 days/wk) combined with daily consumption of the cyclooxygenase-inhibiting drugs acetaminophen (4.0 g/day; n = 11, 64 ± 1 yr) or ibuprofen (1.2 g/day; n = 13, 64 ± 1 yr) unexpectedly promoted muscle mass and strength gains 25-50% above placebo (n = 12, 67 ± 2 yr). To investigate the mechanism of this adaptation, muscle biopsies obtained before and ∼72 h after the last training bout were analyzed for mRNA levels of prostaglandin (PG)/cyclooxygenase pathway enzymes and recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 72 publications
2
68
0
Order By: Relevance
“…The COX-inhibitor consumption also promoted an upregulation of the PGF 2␣ receptor in the muscle of the drug groups (127). This increase coupled with a general training increase in COX-1 and the PGF 2␣ -producing enzymes (PGF 2␣ synthase and PGE 2 -to-PGF 2␣ reductase) (125,127) would make the muscle less susceptible to the same, daily COX-inhibiting drug doses and more sensitive to any PGF 2␣ that was produced following exercise. Whether these responses and muscle adaptations are specific to older individuals and any potential basal inflammatory state or exaggerated response following exercise (21,26,36,80,89,117,118,124) is unclear and needs further investigation.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The COX-inhibitor consumption also promoted an upregulation of the PGF 2␣ receptor in the muscle of the drug groups (127). This increase coupled with a general training increase in COX-1 and the PGF 2␣ -producing enzymes (PGF 2␣ synthase and PGE 2 -to-PGF 2␣ reductase) (125,127) would make the muscle less susceptible to the same, daily COX-inhibiting drug doses and more sensitive to any PGF 2␣ that was produced following exercise. Whether these responses and muscle adaptations are specific to older individuals and any potential basal inflammatory state or exaggerated response following exercise (21,26,36,80,89,117,118,124) is unclear and needs further investigation.…”
mentioning
confidence: 97%
“…Follow-up studies on muscle biopsies obtained from these individuals (125,127) and subsequent ex vivo studies (110) provide some mechanistic clarity about these unexpected COX-inhibitor effects (Fig. 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study suggests that the positive action of NSAIDs on muscle in the elderly could be through the lowering of a constantly elevated systemic level of inflammatory activity. Indeed NSAID ingestion by healthy elderly individuals performing a 12-wk program of resistance training has been shown to eliminate the increase in the muscle gene expression levels of the cytokines interleukin-6 and -10 observed in the placebo group (78). Further studies in humans are required, however.…”
Section: Effects Of Nsaids On Hypertrophy and Protein Synthesismentioning
confidence: 99%
“…Two recent studies of human skeletal muscle have reported abundant gene expression levels of EP4, which were observed to increase further with 12 wk of resistance training, while only infrequent or low gene expression levels of EP1, EP2, and EP3 were detected (62,78). Interestingly, the PGF 2␣ receptor was also detected at the gene level and observed to be upregulated in elderly individuals who performed resistance training for 12 wk in conjunction with ingestion of the NSAID ibuprofen or acetaminophen, while no change was detected in the placebo group (78). Shown in Fig.…”
mentioning
confidence: 98%